Automated Kitchen Management and Provisions Monitoring System Using IoT Technology - Srinivasan Subramanian, K. Vinoth Kumar, T. Jayasankar, Malladi Srinivas (International Journal of Control and Automation, 2020)
The primary purpose of this paper is to provide a user-friendly android application of kitchen monitoring for cooking by using the Internet of Things. Applications are available for fetching the recipes, but this project helps to reduce our mind calculation in choosing the cuisines. This application extracts the kitchens which stored in the Web Service. A sensor node is used for sensing the weight of the grocery container and uploads it to the Web Service. By using this update, the user can choose the cuisine and recipes with the available products and cook. This application can be used from anywhere at any time by making the recipe decisions easier. If a particular grocery is found empty, then its weight is notified as 0, that is, that specific grocery has to be refilled in its container. The main aim of this research is to provide a user-friendly android application that is useful for monitoring the food provisions in the kitchen and also provide different variety of cuisines and recipes based on the availability of ingredients.